Novel Mutations in The Coding Region of The Third Exon of Myostatin (MSTN) Gene in Madura Cattle - irida novianti; Rafika Febriani Putri; Doni Herviyanto; Ahmad Furqon; Wike Andre Septian; Kuswati Kuswati; suyadi suyadi (Jurnal Ilmu-Ilmu Peternakan, 2023)
Molecular information using gene variants could support livestock selection to improve livestock productivity. This study aimed to identify the variants in part of the MSTN gene (part of the third exon coding region), a gene known for its significant effect on muscle growth. DNA was isolated from 95 Madura cattle blood samples collected in Pamekasan, Madura. PCR was used to amplify to MSTN region in part of the third exon, and one-way sequencing was conducted to obtain the sequence from the amplified product. Six SNPs were identified. Four SNPs were novel mutations, and the other two SNPs were recorded in the Ensembl database (rs466598800 and rs211583837). Among the identified novel mutations, one mutation in c.1301G/T caused a stop codon for the TT genotype cattle. However, no cattle carried the TT genotype. Three other mutations in c.1324, c.1373, and c.1399 were missense mutations that change the amino acids Q311L, A318P, and L335B, respectively. Most of the cattle had heterozygote genotypes for all the identified SNPs. It could also be noted that there were sequence differences in the part of the third exon identified between Madura cattle and Zebu cattle (by Tantia et al., 2006).